ANALISIS BANTUAN HIBAH BIBIT SAMBUNG PUCUK TERHADAP PERUBAHAN PERILAKU PETANI KAKAO DI KABUPATEN PINRANG - Andi Yuli Tenriawaru; Nurliani Karman; Nuraeni Nuraeni (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
Analysis Of Chupon Grafting Grand Aid On The Bahavior Of Cocoa Farmers in Pinrang Regency. The research was conducted in June2017 - August 2017 on Duampanua District Pinrang Regency.The purpose of this study was to describe and identify the implementation of chupon grafting aid program in Pinrang Regency, to analyze the level of knowledge and skill of farmers on the assistance of chupon grafting aid program of cocoa sedling, and the participation of the cocoa farmers in the farmer group in Pinrang Regency. This research uses descriptive qualitative method with interview technique to explore information about chupon grafting cacao seedlings, and survey approach to describe the aid pattern, and include several stages of data collection and field observation, data analysis and data processing. The results showed that with the help of chupon grafting affect the behavior of farmers in the form of increased knowledge, skills and participation in farmer groups. Assistance given has been in accordance with the flow of mechanisms that have been in accordance with the Minister of Home Affairs Regulation of the Minister of Home Affairs No. 30 of 2012 and South Sulawesi Governor Regulation No. 55 of 2012.